Clinical study on anti-fungal drug activity against clinically isolated strains of oral Candida species - Kamikawa, Yoshiaki; Nagayama, Tomohiro; Fujisaki, Junichi; Hirabayashi, Daisuke; Kawasaki, Kiyotsugu; Hamada, Tomofumi; Mori, Youichiro; Kamikawa, Yasuko; Mukai, Hiroshi; Sato, Tomoaki; Sugihara, Kazumasa (Oral Science International, 2013)
The present study was undertaken to evaluate the anti-fungal activity of amphotericin B (AMPH-B), flucytosine (5-FC), fluconazole (FLCZ), miconazole (MCZ), itraconazole (ITCZ), and micafungin (MCFG) against clinically isolated Candida strains from oral candidiasis (OC) patients and to collect information useful for the treatment of OC. The study includes 116 strains of Candida isolated from patients. The Candida species were identified by polymerase chain reaction. The minimum inhibitory concentration (MIC) of each drug against each Candida species was determined. Of the 106 participants (30 males and 76 females), 57 had OC, including 42 cases of pseudomembranous OC, 11 cases of erythematous OC, 2 cases of hypertrophic OC, and 2 cases of mixed pseudomembranous/erythematous OC. The Candida species isolated were Candida albicans (93 strains), C. glabrata (19 strains), and C. tropicalis (4 strains). AMPH-B and 5-FC had low MIC values against all species of Candida and a low incidence of resistance development. In some species of Candida, FLCZ and ITCZ showed high MICs, but MCZ had a low MIC value. AMPH-B, MCZ, and ITCZ prescribed to OC patients were effective against OC with respect to alleviation of OC symptoms. MIC values of anti-fungal drugs against Candida strains isolated from OC patients were obtained and the 3 anti-fungal drugs given to OC patients were found to be effective against OC in spite of differences in their MIC values and in the number of resistant strains (or strains with a high MIC value).